2022
DOI: 10.3389/fcimb.2022.989188
|View full text |Cite
|
Sign up to set email alerts
|

Saliva microbiome changes in thyroid cancer and thyroid nodules patients

Abstract: ObjectiveThyroid disease has been reported to associate with gut microbiota, but the effects of thyroid cancer and thyroid nodules on the oral microbiota are still largely unknown. This study aimed to identify the variation in salivary microbiota and their potential association with thyroid cancer and thyroid nodules.MethodsWe used 16S rRNA high-throughput sequencing to examine the salivary microbiota of thyroid cancer patients (n = 14), thyroid nodules patients (n = 9), and healthy controls (n = 15).ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Previous studies showed that Alloprevotella was significantly enriched in oral squamous cell carcinoma tissues [ 45 ] and Alloprevotella was more in outer tumor tissues of oral cancer [ 46 ]. Jiao et al found that compared to normal tissues, Alloprevotella was significantly increased in thyroid cancer tissues [ 47 ]. Wang et al on the other hand, observed significant Alloprevotella enrichment in the intestinal mucosa of azoxymethane and dextran sulfate sodium-induced model of ulcerative colitis carcinogenesis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Alloprevotella was significantly enriched in oral squamous cell carcinoma tissues [ 45 ] and Alloprevotella was more in outer tumor tissues of oral cancer [ 46 ]. Jiao et al found that compared to normal tissues, Alloprevotella was significantly increased in thyroid cancer tissues [ 47 ]. Wang et al on the other hand, observed significant Alloprevotella enrichment in the intestinal mucosa of azoxymethane and dextran sulfate sodium-induced model of ulcerative colitis carcinogenesis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 20-year follow-up study in the UK, patients with elevated TPOAb levels had a higher progression rate to overt hypothyroidism compared to TPOAb-negative patients [ 39 ]. Interestingly, there is evidence to support an association between TPOAb level and the enrichment of oral microbiota in patients with thyroid nodules [ 40 ]. Despite the oral and gut microbiome communities having distinct taxonomic features at the phylum and genus levels [ 41-43 ], prior findings regarding the gut microbiome still support observations about the oral microbiome in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus and Porphyromonas are abundant in the gut microbiome of patients with thyroid cancer, and these genera are also enriched in patients with thyroid nodules compared to healthy controls [ 20 ]. Saliva microbiome analysis showed that genus Acinetobacter was more enriched in patients with thyroid cancer than healthy controls [ 21 ].…”
Section: Discussionmentioning
confidence: 99%